(3ecGJHI Edi GdTjN CHj GdeYGdis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUdJ ecGJHI GdTjN GdWGgQ GdRci Ph GdfaS GdSGcfI hGdYbd GdRGgQ GdGHi s
(3BNQgG (B:s
(3adGjVLY GdTjN GdNjQ ajeG BeQg ef GdeQGYGg dCNhJg hHfhG Yeg GdeRGQYjf ef aUd GdbSeI hGdeMGSHI hGdMeO ddg ceG gh Ggdg hUdhGJg Ydi QShdg hGdg hSde JSdjekG JSdjekG hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis